Religiosity, Emotional Intelligence, and Self-Control: A Mediation Analysis in Islamic Higher Education Contexts - Noer Hidayah (Journal An-Nafs: Kajian Penelitian Psikologi, 2025)
This study examines the relationship between religiosity and self-control, with emotional intelligence examined as a mediating mechanism. Although prior research has identified associations among these variables, most studies have relied on bivariate analyses and have not sufficiently explored the psychological processes underlying these relationships. A quantitative research design was employed, involving first-year undergraduate students from the Faculty of Tarbiyah at IAIN Kediri. The population consisted of students enrolled in the 2024/2025 academic year, from which 272 participants were selected using simple random sampling. Data were collected using validated self-report questionnaires measuring religiosity, emotional intelligence, and self-control. Path analysis was applied to test both direct and indirect relationships among the variables using SPSS. The findings indicate that religiosity had a strong direct effect on emotional intelligence (β = 0.829) and a modest but statistically significant direct effect on self-control (β = 0.191). Emotional intelligence, in turn, emerged as a strong predictor of self-control (β = 0.639) and significantly mediated the relationship between religiosity and self-control, with an indirect effect of 0.5297. The indirect pathway through emotional intelligence exceeded the magnitude of the direct effect, underscoring the central role of emotional competencies in translating religious commitment into self-regulatory behavior. These results suggest that religiosity contributes to self-control primarily through its influence on emotional intelligence, highlighting emotional intelligence as a key psychological mechanism within Islamic educational contexts. The findings extend existing research by integrating religiosity, emotional intelligence, and self-control within a single mediation model and offer practical implications for character and student development in Islamic higher education. Educational initiatives that simultaneously strengthen religious values and emotional competencies may enhance students’ capacity for adaptive self-regulation and disciplined behavior.